Economic viability of community-based forest management for certified timber production in southeastern Tanzania. (August 2021) - Frey, Gregory E.; Charnley, Susan; Makala, Jasper
Highlights: 14 FSC-certified community forests sell timber and provide community payments, but depend on external financial support. Revenues have increased and costs decreased over time, trending towards better financial outcomes and independence. Still, in order to achieve full financial independence, they will need to sell more timber, decrease costs, or add value. Despite stocks of valuable timber, sales are constrained by low domestic demand and competition with uncertified sources. Costs are high because of certification and regulations requiring outside experts, and community payments. Abstract: Community-based forest management has become increasingly widespread in Africa since the 1990s as an approach to conserving local forests while contributing social and economic benefits to local communities. Community forests (CFs) can sell forest goods and services to generate revenue for community benefit. Increased understanding of whether and how CFs can be economically viable is important for assessing their potential to alleviate rural poverty and deliver benefits to local communities. Questions of viability of commercial timber-producing CFs largely have not been addressed to date in the African context, and have important ramifications for community members, government decision-makers, and external donors. We conducted an economic and financial evaluation of a group of CFs in southeastern Tanzania that sell high-value tropical timber from Forest Stewardship Council–certified community forests. We found that this group of CFs currently is not economically viable, with forest management costs 2.6 times forest revenues over the five-year study period. However, revenues appeared to be increasing and costs decreasing over the period, and in the final two years costs were about 1.5 times revenues. The largest forest management costs were related to CF establishment and maintenance, which may be driven by the cost of relying on external experts; still, these costs decreased over time. Community transfer payments – used to support local development projects or community members – were the second largest cost category, but are unrelated to forest management. Based on current prices and rates of fixed and variable costs, timber sales would have to increase almost tenfold for these communities to be economically viable independent of external donations; however, some combination of increased timber sales, increased training and capacity, capped community payments, and added timber value could be successful in achieving economic viability. Increased sales seem to be the most direct approach, but is constrained by lack of demand at present, so marketing is needed.